بەدواداهاتنى کات لە کەڵەڕستەدا - على, بەکر عمبر; فرج, هۆگر محمود (Sulaimani Journal for Humanities, 2002)
* Agreement of verb tenses in compound sentences The paper deals with verbs from the perspective of their tense agreement in compound sentences, we know that every compound sentence from another's, for example the tense of the first verb in the first sentence may be “past“ and the second “present “ Given that past simple tense in kurdish has four different forms” simple ,continuous , far ,perfect ، "we , hereby attempt an answer to the following question: Is it possible for a compound sentence to contain a verb in the far past as a second in the continuos past؟ The paper deals , in details , with this case, giving illustrative examples , however we must point out that this topic has not been touched upon previously, and all that has been written on it is no more than sporadic remarks . Finally, the writer gives a list of the conclusions he has drawn .